Study on Downhole Throttling Characteristics of High Water Content Gas. (24th January 2022) - Zheng, Jie; Li, Zhenzhen; Dou, Yihua; Zhang, Yarong; Bi, Cheng; Yang, Xu; Li, Jiahui
Abstract : In order not to hinder gas production, we usually hope that the bottom hole effusion can be discharged to the surface with high-pressure natural gas. For the production data of high water content gas wells, the problems of insufficient water content and liquid-carrying capacity affecting gas well production should be considered. Based on the wellbore gas-liquid two-phase pipe flow theory and heat transfer theory, the temperature and pressure coupling prediction model of a high water-bearing gas well is established. Combined with the downhole throttling mechanism and gas-liquid two-phase homogeneous flow theory, the temperature and pressure field distribution model is established. The results show that compared with the Ramey model and Hassan and Kabir model, the temperature and pressure coupling prediction model of high water-bearing gas wells established in this study has the smallest coefficient of variation in the four groups of data tests. Based on this, the effects of different working conditions and choke diameter on downhole throttling characteristics of high water-bearing gas wells are analyzed. The findings of this study are helpful to better predict the wellbore temperature and pressure coupling of high water-bearing gas wells and provide more effective help for the smooth production of gas wells.